Roles of Filipino stay-at-home fathers in female breadwinner households - Del Rosario, Ciara Leila R.; Urquia, Marian Joy P.
This qualitative study aims to identify the roles of the stay-at-home fathers (SAHFs) in female breadwinner households. A total of 15 Filipino SAHFs residing in the National Capital Region participated in in-depth interviews and the data from it were analyzed through thematic analysis. The findings revealed five distinct themes describing the circumstances leading to the SAHF arrangement: 1) opportunity for wife to work, while husband lacks opportunity, 2) difficulty to find a reliable carer of a child, 3) health-related constraints, 4) voluntarily left work, and 5) passion-driven calling. The SAHF arrangement was primarily influenced by their wife’s employment opportunities. The study also examines the roles of SAHFs: 1) home manager, 2) nurturer, 3) partner, and 4) role model. Notably, not all SAHFs identify as nurturers however, they all identify as home managers. Perceptions of SAHFs regarding their roles revolve around 1) ensuring their family well-being and success, 2) their preference to work, 3) breaking patterns of their childhood experiences, and 4) navigating gender-atypical roles. Some SAHFs embrace the concept of detraditionalizing fatherhood however, some SAHFs still perceive their roles through traditional gender norms. Given these findings, this study contributes to redefining the concept of fatherhood in the Philippines.